Analysis of Dynamic Governance In The Implementation of Hajj at The Office of The Ministry of Religious Affairs of Blitar Regency - Dwi Ayu Damayanti; Slamet Muchsin; Hayat Hayat (PT. Publikasiku Academic Solution, 2024)
Economic growth prioritizes building and strengthening sectors in the economic field by developing, improving and maximizing resources. West Java Province is one of the provinces that has a large economic contribution to the national Gross Domestic Product (GDP). The purpose of this study was to determine the agricultural sub-sector included in the leading sector (base) and to determine the shift of the agricultural sub-sector in West Java Province and the classification of Klassen typology in the economic sector in West Java Province. This study uses secondary data in the form of the value of the Gross Regional Domestic Product of West Java Province and the Indonesian Gross Domestic Product at constant 2010 prices by business field from 2019 to 2023. The data is processed using location quentient (LQ) analysis tools, shift share analysis (SSA) and Klassen typology analysis. The results of the location quentient (LQ) analysis show that the Agriculture, Forestry and Fisheries sector is a non-base sector in West Java Province. The results of shift share analysis (SSA) show that the Agriculture, Forestry and Fisheries Sector has a positive influence on regional economic growth (Nij) of Rp. 12,925 billion, Industry Mix (Mij) of Rp. -5,183 billion and competitive advantage (Cij) of Rp. 910,074 billion. The results of the Klassen typology analysis show that the Agriculture, Forestry and Fisheries Sector is a developed but depressed sector, so it is hoped that the West Java Provincial Government will accelerate growth by increasing output and absorbing more labor.